If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2(7x+6)=-12-14x
We move all terms to the left:
-2(7x+6)-(-12-14x)=0
We add all the numbers together, and all the variables
-2(7x+6)-(-14x-12)=0
We multiply parentheses
-14x-(-14x-12)-12=0
We get rid of parentheses
-14x+14x+12-12=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0
| 3x=4+28 | | 4(m-1)=8(m-1)+12 | | 9v+54=18v | | y/10-3=5 | | x+24+2x=2-2x-4 | | -5-19p=-17p-13-2p | | 1(2y+-1)=-9 | | 6+15x=-3(-5x-2) | | -8u-8=-4(u+6) | | 8(s-3)=-84 | | 4+2x=2(-x+2)-8 | | b-4/2=b+1/4 | | 6+15x=-3 | | 6-4n=-409 | | -14x+11-11=-17-14x | | 6-4n=-409 | | 3x-4-4x=3x-4-2x-6x | | -20+x=20+20-9x | | 48=-v+188 | | 36-x=192 | | -8x-19=-4-15-8x | | 7x-17=x+6+x+2 | | 7x-12.73=6x+12.27 | | 5-c/8=10 | | 98=-y+223 | | m/2+8=4 | | x/75=5 | | 10+4f-2f=2f+6 | | x/4=2(3) | | -7x-4(5-3x)=3(x-4)-8 | | 288-v=145 | | 5^x+10)(2^x-0.0625)=0 |